Surface Flocculation as a New Tool for Controlling Adsorption Processes - Miloslav Milichovský; Bretislav Češek (Adsorption Science & Technology)
The dyeing of modified pulp, particularly with regard to the mechanism involved, was studied. The reaction mechanism for the modification of cellulose fibres in aqueous solution by cationic agents was also described. The results obtained were expressed in the form of adsorption isotherms. The capture of molecules, colloidal particles, etc. during the adsorption processes involving modified pulp could be explained by two possible mechanisms: (i) aggregation (coagulation or flocculation) in solution followed by adsorption and (ii) surface aggregation (coagulation or flocculation). Surface aggregation appeared to be the most likely for pulp with a low degree of modification. The typical Langmuir adsorption isotherm correlated the data obtained for unmodified pulp very well.